1997
DOI: 10.1177/082585979701300103
|View full text |Cite
|
Sign up to set email alerts
|

Home and Inpatient Hospice Care of Terminal Head and Neck Cancer Patients

Abstract: The objective is to evaluate and compare data on a cohort of terminal head and neck cancer (HNC) patients from both home and hospital-based hospice programs and to define the particular problems and needs of those patients. The setting was a tertiary academic referral centre in Tel Hashomer, Israel. We carried out a retrospective survey of patient charts based on hospice databases and death certificates of the hospital tumor registry. Charts of 102 HNC patients admitted to the hospice between 1988 and 1994 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…This is not surprising and correlates with the reported prevalence of oral candidiasis incurred in up to 85% 3 with the rate of incidence most likely approaching 90% as the patient with cancer nears death 14. Previous retrospective chart studies by our group on a cohort of terminal head and neck carcinoma patients reported that oral candidiasis was seen and treated in 10–14% of inpatients and 2% of home care patients 15, 16. Because patients with head and neck carcinoma are more prone to oral complications due to the basic nature of their disease and treatment, we believe that this lower incidence rate arose from inadequate diagnosis with regard to oral symptoms recorded in the patient charts that were analyzed retrospectively.…”
Section: Discussionmentioning
confidence: 97%
“…This is not surprising and correlates with the reported prevalence of oral candidiasis incurred in up to 85% 3 with the rate of incidence most likely approaching 90% as the patient with cancer nears death 14. Previous retrospective chart studies by our group on a cohort of terminal head and neck carcinoma patients reported that oral candidiasis was seen and treated in 10–14% of inpatients and 2% of home care patients 15, 16. Because patients with head and neck carcinoma are more prone to oral complications due to the basic nature of their disease and treatment, we believe that this lower incidence rate arose from inadequate diagnosis with regard to oral symptoms recorded in the patient charts that were analyzed retrospectively.…”
Section: Discussionmentioning
confidence: 97%
“…12 Terminally ill patients possess local and systemic predisposing factors to oral candidal infection. 15,16 Because patients with head and neck carcinoma are more prone to oral complications due to the basic nature of their disease and treatment, we believe that this lower incidence rate arose from inadequate diagnosis with regard to oral symptoms recorded in the patient charts that were analyzed retrospectively. 13 The majority of the patients included in this study had oral candidiasis (94%).…”
Section: Discussionmentioning
confidence: 99%
“…8 The importance of palliative care teams and the utilization of hospice services cannot be overstated. 9,10 Given the poor prognosis of many advanced tumors, initial treatments, even those with seemingly curative intent, might be considered by some to be palliative. 11 Timon and Reilly 12 estimate that 20% of patients would qualify for palliative care at the time of initial diagnosis, with an average survival of 5 months within this cohort.…”
Section: Discussionmentioning
confidence: 99%